Sustainable sanitation: Screening methods of electrolysing parameters for a custom-built electrolysed water generator - Khalid, Nurul Izzah; Sulaiman, Nurul Shaqirah; Ab Aziz, Norashikin; Taip, Farah Saleena; Sobri, Shafreeza; Mahmud Ab Rashid, Nor Khaizura (Elsevier, 2022)
Sanitation is a compulsory procedure in the food industry. As it involves production downtime, it imposes overhead costs. One way to obtain higher profit margins is to cut the overhead costs of sanitation. Eco-innovative cleaners and sanitisers such as electrolysed water have a high potential to reduce sanitation costs. The only ingredients of electrolysed water are salt and distilled water. Some major food industries invest in expensive commercial electrolysed water generators to produce different types of electrolysed water (acidic, alkaline, and neutral). Smaller food industries can install an electrolysed water generator independently, but they need to determine the optimum and most economical electrolysing parameters. Different electrolysed water generators employ different electrolysing parameters to produce electrolysed water with the same physical and chemical properties. Thus, in this work, electrolysing parameter screening methods are demonstrated. A laboratory-scale electrolysed water generator was used to investigate the effects of different electrolysing parameters (voltages (1–20 V), electrolysis times (1–15 min), and sodium chloride concentrations (0.05–3%)) on the physical and chemical properties (pH, oxidation-reduction potential (ORP), and available chlorine concentration (ACC)) of electrolysed water (both acidic and alkaline). These screening methods were essential to determining the range of electrolysing parameters to use for the optimisation experiments and ascertaining the generator's limit. The subsequent optimisation experiments aimed to ensure the generator could be used for a long period and that economical usage conditions were achieved. The screening experiments helped to reduce the parameter variations in these experiments and provide reliable data on electrolysed water properties.